Depicting the contrasts while remaining neutral in “The Portrait of a Lady” - Moghadam, Davood Mohammadi; Wan Yahya, Wan Roselezam (KY Publications, 2014)
Among the subjects and the themes in the works of Henry James, his international theme of ‘America versus Europe’ is the most recurrent one. James’ literary career is divided into three periods, and the international theme is the main subject of the first and the third period. Through his international theme, James had tried to show the contrasts which he believed to exist between America and Europe. The Portrait of a Lady is his most well-known masterpiece; which again deals with the international theme of America versus Europe. All parts of this novel, like its characters, settings and events are used like a chain to show the contrast between America and Europe. But this study is going to discuss that although James tries to show the contrast between America and Europe, he remains neutral towards America and Europe completely skillfully. He defined neither America nor Europe to be the superior or the inferior one. As a realist writer, he only shows the reality about America and Europe and leaves it to his audiences to decide about them. The main contrast in this novel is between American morality and innocence and European high culture and sophistication.